(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This research explores credibility and user perception of national Hindi television news channels of India. Previous studies indicate that media use and its credibility are positively co-related. Some studies also suggest that Hindi news channels sensationalise its content for the sake of TRPs. This research includes quantitative and qualitative approach to find the message creator and its receiver’s perspective about the credibility of national Hindi television news channels. This study’s research hypothesis is that users’ perceived credibility of a Hindi television news channel depends on their awareness of fake news and echo-chamber effect. The study finds that echo-chamber effect is directly affecting the perceived credibility of Hindi news channel but if debunked fake news is broadcasted from user’s favourite Hindi news channel, their awareness of fake news is not affecting their perceived credibility. To know the user’s perspective, a survey on randomly selected audience of Delhi-NCR is conducted. For qualitative analysis, in depth interview of senior television editors have been done. This study concludes that Hindi news channel’s journalism is highly dependent on TRP driven revenue generation, which is pushing it to popularity driven, instead of credibility driven journalism. This study has related content analysis of fact-check outlets with the credibility of Hindi news channels. Results show that Hindi news channels’ fake stories are debunked by these fact check outlets, but still Hindi news channels don’t care about their story being debunked. Senior TV editors are also accepting this fact, which is a serious concern for the fourth pillar of our democracy.